Organização do trabalho e saúde mental : o caso dos servidores técnico-administrativos de um Instituto Federal - Lemos, Thiago da Silva Duarte (2023)
Using the Psychodynamics of Work as a theoretical reference, this study aims to analyse the impacts of work organization on the mental health and psychosocial wellbeing of administrative technical staff at the IFPB (acronym for Instituto Federal da Paraíba, a professional and technological college in north-east of Brazil) headquarters. The study is justified by the alarming increase in mental health issues in today's society, affecting all spheres of individuals' lives, including work, as work and mental health revolve around a common center. In the initial stages, this research provides a historical overview of professional and technological education in Brazil, highlighting the mission of the Rede Federal de Educação Profissional, Científica e Tecnológica (Federal Network of Professional, Scientific, and Technological Education, in free translation), which encompasses the Federal Institutes. The study offers insights into the career of technical-administrative education staff ("técnico-administrativos em educação" in portuguese, abbreviated as "TAEs") and their fundamental role in the functioning of these institutions. The theoretical framework continues with a discussion of the dialectical relationship between work and mental health, and how the precarization of work in contemporary society is at the root of workers' psychological suffering. At this point, the study reviews the most recent research on mental health and the work of TAEs, inevitably delving into the theme of Quality of Work Life. With a quantitative and qualitative focus, this study employed methods such as bibliographic/documentary research and survey research for data collection. The study revealed a high prevalence of mental and behavioral disorders in the surveyed population, mainly anxiety and depression disorders; however, low psychosocial risks related to work were observed. The existing mental health care programs at IFPB and their reach to the administrative technical staff at the headquarters were examined. Based on this analysis, a Psychosocial Risk Map of the IFPB headquarters is presented, and improvements in the realm of psychosocial care and new policies aimed at the well-being of this group of staff are proposed.